2017
DOI: 10.1007/s11739-017-1660-6
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran etexilate: appropriate use in patients with chronic kidney disease and in the elderly patients

Abstract: Dabigatran etexilate (DE) is a direct thrombin inhibitor, which has been approved for the treatment of non-valvular atrial fibrillation (AF), and for the prevention and treatment of venous thromboembolism (VTE). Despite large randomized clinical trials and independent observational studies providing robust data concerning DE safety and efficacy, some physicians still perceive mild-to-moderate renal impairment and old age as a relative contraindication to its use. In this article, we review the available scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In fact, although the fixeddose regimen of DOACs offers a clear practical advantage, physicians are likely to question the safety of fixed-dose administration in frail subgroups of patients. In line with these observations, among others, Molteni and co-workers, when reviewing available evidence on the use of dabigatran in patients with CKD and in the elderly, pointed out that that despite in patients with no contraindication to its use, the clinical benefit of dabigatran versus VKAs is independent of renal function, some physicians still perceive mild-tomoderate renal impairment as a relative contraindication to DOAC' use [62].…”
Section: Direct Anticoagulants Agentsmentioning
confidence: 89%
“…In fact, although the fixeddose regimen of DOACs offers a clear practical advantage, physicians are likely to question the safety of fixed-dose administration in frail subgroups of patients. In line with these observations, among others, Molteni and co-workers, when reviewing available evidence on the use of dabigatran in patients with CKD and in the elderly, pointed out that that despite in patients with no contraindication to its use, the clinical benefit of dabigatran versus VKAs is independent of renal function, some physicians still perceive mild-tomoderate renal impairment as a relative contraindication to DOAC' use [62].…”
Section: Direct Anticoagulants Agentsmentioning
confidence: 89%
“…A meta-analysis published by some researchers evaluated the safety and efficacy of dabigatran, apixaban and rivaroxaban in patients with renal insufficiency. DOAC use was compared to warfarin in patients with mild (defined as eGFR 50–79 mL/min) and moderate (defined as eGFR of 30–49 mL/min) renal impairment and found that DOAC use reduced the risk of stroke, systemic embolism and major and non-major bleeding[ 31 ]. Dabigatran 150 mg twice daily was approved by the FDA for atrial fibrillation for patients with eGFR > 30 mL/min and 75 mg twice daily for patients with eGFR 15-29 mL/min[ 6 ].…”
Section: Consideration In Kidney Diseasementioning
confidence: 99%
“…Dabigatran 150 mg twice daily was approved by the FDA for atrial fibrillation for patients with eGFR > 30 mL/min and 75 mg twice daily for patients with eGFR 15-29 mL/min[ 6 ]. Based on real-world data, the use of DOACs is strongly discouraged in patients with end-stage renal disease (ESRD)[ 31 ]. After RE-COVER, RE-COVER II, RE-MEDY, and RE-SONATE trials, the FDA approved dabigatran 150 mg BID (after 5-10 d of parenteral anticoagulation) for the treatment of DVT and PE in patients with eGFR > 30 mL/min and recommends against the use in patients with eGFR < 30 mL/min[ 9 ].…”
Section: Consideration In Kidney Diseasementioning
confidence: 99%
“…Therefore, a patient’s advanced age or renal insufficiency should not discourage physicians from initiating or maintaining chronic oral anticoagulation with DOACs in patients with AF. 68 …”
Section: Renal Failure and Doac Use In The Covid-19 Pandemicmentioning
confidence: 99%